2014
DOI: 10.1007/s11999-014-3587-9
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Costs of Total Hip Arthroplasty for Developmental Dysplasia of the Hip

Abstract: Level IV, economic and decision analyses. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…Longitudinal studies have revealed that degenerative changes induced by hip dysplasia develop more rapidly than in other predisposing conditions [77]. Total hip replacement (THR) is a surgical procedure that is most often performed in treating symptomatic advanced osteoarthritis, especially in younger age [78][79][80][81][82]. The diagnosis of DDH in first-order relative increases a chance for THR by the age of 65 [83].…”
Section: Natural History Of Ddh: Prevention Versus Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies have revealed that degenerative changes induced by hip dysplasia develop more rapidly than in other predisposing conditions [77]. Total hip replacement (THR) is a surgical procedure that is most often performed in treating symptomatic advanced osteoarthritis, especially in younger age [78][79][80][81][82]. The diagnosis of DDH in first-order relative increases a chance for THR by the age of 65 [83].…”
Section: Natural History Of Ddh: Prevention Versus Operationmentioning
confidence: 99%
“…Recent studies show that average hospital cost for primary THR secondary to DDH is higher than in other cases. Also, the severity of DDH additionally increases those expenses [79,84]. If DDH is diagnosed early and the treatment was nonoperative, the rate of osteoarthritis at long-term follow-up is twice lower than after open reduction [81].…”
Section: Natural History Of Ddh: Prevention Versus Operationmentioning
confidence: 99%
“…Hip arthroplasty for DDH is complex surgery, and the cost of this procedure is more than a hip arthroplasty for primary osteoarthritis. Increased degree of dysplasia according to Crowe classification has been associated with higher costs [65].…”
Section: Femoral Partmentioning
confidence: 99%
“…However, there are still a few patients who suffer re-dislocation, residual hip dysplasia, residual acetabular dysplasia or osteoarthritis (Carney et al 2005, Thomas et al 2007. Most of these patients have to undergo total hip arthroplasty before the age of 50, causing the patients themselves and their family great psychological and economic burden (Ashraf et al 2014). In-depth analysis of the molecular mechanism underlying development of this disease and study of the proteins or genes that play key roles in this process should help with screening and identification of these patients.…”
Section: Introductionmentioning
confidence: 99%